The Potential Effects on Microbiota and Silage Fermentation of Alfalfa Under Salt Stress - Lu, Qiang; Wang, Zhen; Sa, Duowen; Hou, Meiling; Ge, Gentu; Wang, ZhiJun; Jia, Yushan (Frontiers in Microbiology, 2021)
This study investigated the fermentation quality of alfalfa grown in different salt stress regions in China. Following the production of silage from the natural fermentation of alfalfa, the interplay between the chemical composition, fermentation characteristics, and microbiome were examined to understand the influence of these factors on the fermentation quality of silage. The alfalfa was cultivated under salt stress with the following: (a) soil content of ＜1‰ (CK); (b) 1‰-2‰ (LS); (c) 2‰-3‰ (MS); (d) 3‰-4‰ (HS). The pH of the silage was high (4.9-5.3), with lactic acid content was high (26.3-51.0 g/kg DM). As the salt stress increases, the NA+ of the silages was higher (2.2-5.4 g/kg DM). The bacterial alpha diversities of the alfalfa silages were distinct. There was a predominance of desirable genera including Lactococcus and Lactobacillus in silage produced from alfalfa under salt stress, this led to better fermentation quality. The chemical composition and fermentation characteristics of the silage were closely correlated with the composition of the bacterial community. Furthermore, NA+ was found to significantly influence the microbiome of the silage. The results confirmed that salt stress has a great impact on the quality and bacterial community of fresh alfalfa and silage. The salt stress and plant ions were thus most responsible for their different fermentation modes in alfalfa silage. The results of the study indicate that exogenous epiphytic microbiota of alfalfa under salt stress could be used as a potential bioresource to improve the fermentation quality.